1999
DOI: 10.1074/jbc.274.29.20103
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of a Heparan Sulfate Subunit to the Interleukin-1 Receptor Complex

Abstract: Background:Anthracycline is an antitumor agent of the topoisomerase inhibitor family. Results: Doxorubicin inhibits the expression of hypoxia-inducible genes, suppresses HIF-dependent migration of target tumors, and dampens angiogenic response of the host heart. Conclusion: Doxorubicin blocks recruitment of HIF heterodimers to the enhancer and inhibits hypoxia response. Significance: The pleiotropic effect of doxorubicin on HIF signaling provides a clue for understanding efficacy and toxicity of cancer chemoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 73 publications
5
34
0
Order By: Relevance
“…We have reported previously that IL-1 receptors are localized to focal adhesions in cells attached to fibronectin and that IL-1 causes rapid phosphorylation of talin and transient changes in cytoskeletal organization (26,48,49). Further, recent data from our laboratory show that there is an attachment-mediated recruitment of a cell surface heparan sulfate to the IL-1 receptor complex, correlating with effects on signaling (29). We therefore speculate that box 3 is (part of) a site that mediates binding of IL-1RI to one or more focal adhesion or cytoskeletal components.…”
Section: Figmentioning
confidence: 64%
See 1 more Smart Citation
“…We have reported previously that IL-1 receptors are localized to focal adhesions in cells attached to fibronectin and that IL-1 causes rapid phosphorylation of talin and transient changes in cytoskeletal organization (26,48,49). Further, recent data from our laboratory show that there is an attachment-mediated recruitment of a cell surface heparan sulfate to the IL-1 receptor complex, correlating with effects on signaling (29). We therefore speculate that box 3 is (part of) a site that mediates binding of IL-1RI to one or more focal adhesion or cytoskeletal components.…”
Section: Figmentioning
confidence: 64%
“…A recent report has shown that IRAK (Ϫ/Ϫ) cells reconstituted by transfection with a kinase (Ϫ) IRAK mutant respond to IL-1 and that in these cells IRAK is phosphorylated in response to IL-1 (27). Indeed it has been suggested that the kinase activity of IRAK-1 and IRAK-2 is not required for IL-1 signaling (29). These data suggest that there is at least one protein kinase other than IRAK-1 or IRAK-2, possibly IRAK-M, associated with the IL-1 receptor complex, and which by inference participates in IL-1 signaling (46).…”
Section: Figmentioning
confidence: 99%
“…This likely involves receptor-associated regulators of the GTPases such as the putative Rap/GTPase activating protein (GAP), IIP-1 (38). Furthermore, the attachment dependence suggests that activation could be induced as a consequence of recruitment of the matrix-dependent, accessory receptor component to the IL-1 receptor complex (17) and thus result from co-regulation through integrin mediated activities. Such effects could be induced following selective activation of signaling components by structural events, as suggested by our data demonstrating specificity for the activities mediated through receptor-associated proteins MyD88 and TRAF6.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of IL-1 receptors are located at focal adhesions (16), and matrix attachment results in alterations in IL-1 receptor function (17). Subsequent IL-1-induced signal transduction and gene activation are regulated by cell attachment and the cytoskeleton (18 -20).…”
mentioning
confidence: 99%
“…Earlier studies have documented pronounced effects of PDGF on type I IL-1 receptor levels (Bonin and Singh, 1988). We have recently demonstrated that matrixinduced enhancement of inflammatory responses cor-relates with recruitment of an attachment-dependent IL-1 receptor complex component, constituting a heparan sulfate (Valles et al, 1999). This study investigates the role of PDGF in regulation of this novel IL-1 receptor component in SMCs.…”
mentioning
confidence: 99%